Chemodiversity of Nepeta menthoides Boiss. & Bohse. essential oil from Iran and antimicrobial, acetylcholinesterase inhibitory and cytotoxic properties of 1, 8-cineole chemotype. Issue 22 (17th November 2018) - Kahkeshani, Niloofar; Hadjiakhoondi, Abbas; Navidpour, Latifeh; Akbarzadeh, Tahmineh; Safavi, Malihe; Karimpour-Razkenari, Elahe; Khanavi, Mahnaz
Abstract: The essential oil of Nepeta menthoides Boiss. & Bohse., from Iran, was analysed by GC/MS. Two types of multivariate analyses were done based on the chemical composition of the investigated sample in this study and 12 other samples reported in the literature to show the chemodiversity in essential oil composition. Antimicrobial, acetylcholinesterase inhibitory and cytotoxic activities of the essential oil and its major component were assessed. Twenty-one compounds were identified, representing 96.81% of the total oil and the major constituent was 1, 8-cineole (70.06%). Multivariate analyses revealed two chemotypes, i.e. nepetalactone and 1, 8-cineole. The essential oil of the sample investigated in this study which was a 1, 8-cineole chemotype and 1, 8-cineole showed moderate antimicrobial activity and significantly inhibited the activity of acetylcholinesterase enzyme. Cytotoxicity evaluation against three breast cancer cell lines showed a potent inhibitory activity. Further investigations are necessary to confirm the variety in several populations of N. menthoides . Abstract :